2017
DOI: 10.1002/2017ja024615
|View full text |Cite
|
Sign up to set email alerts
|

Solar Illumination Control of the Polar Wind

Abstract: Polar wind outflow is an important process through which the ionosphere supplies plasma to the magnetosphere. The main source of energy driving the polar wind is solar illumination of the ionosphere. As a result, many studies have found a relation between polar wind flux densities and solar EUV intensity, but less is known about their relation to the solar zenith angle at the ionospheric origin, certainly at higher altitudes. The low energy of the outflowing particles and spacecraft charging means it is very d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The dipole tilt angle modulates the solar zenith angle (SZA) and hence the solar irradiation over the polar cap around the dipole axis. This effect has been addressed in both simulations (e.g., Barakat et al, 2015;Glocer et al, 2012;Su et al, 1998) and observations (e.g., Kitamura et al, 2011;Li et al, 2017Li et al, , 2018Maes et al, 2017). Furthermore, the dipole tilt angle also influences magnetosphere-ionosphere coupling as simulated by Cnossen and Richmond (2012).…”
Section: Introductionmentioning
confidence: 99%
“…The dipole tilt angle modulates the solar zenith angle (SZA) and hence the solar irradiation over the polar cap around the dipole axis. This effect has been addressed in both simulations (e.g., Barakat et al, 2015;Glocer et al, 2012;Su et al, 1998) and observations (e.g., Kitamura et al, 2011;Li et al, 2017Li et al, , 2018Maes et al, 2017). Furthermore, the dipole tilt angle also influences magnetosphere-ionosphere coupling as simulated by Cnossen and Richmond (2012).…”
Section: Introductionmentioning
confidence: 99%
“…The outflow increased to a maximum of 2.7 × 10 26 /s during the peak phase of the storm that they investigated. Maes et al (2017) observed a strong dependence of the ion velocity and density on the solar zenith angle. Li et al (2013) have investigated the transport of cold ions between the polar cap ionosphere and the plasma sheet.…”
Section: Wake Effects and Ion Outflowmentioning
confidence: 94%
“…Numerous studies have employed the above technique of combining EFW and EDI measurements to study the outflow of cold ions (André et al, 2015;Engwall et al, 2008Engwall et al, , 2009Haaland et al, 2012Haaland et al, , 2015Li et al, 2012Li et al, , 2013Li et al, , 2017Li et al, , 2018Maes et al, 2017).…”
Section: Wake Effects and Ion Outflowmentioning
confidence: 99%
“…Heating due to solar illumination increases the ambipolar electric field that enables the polar wind outflow. The dependence of the outflow on solar zenith angle (SZA) is seen in both simulations (Glocer et al, , ) and observations (Abe et al, ; Kitamura et al, ; Maes et al, ; Su et al, ). Daily and seasonal changes in the geomagnetic dipole tilt angle modulate illumination over the source region of the polar wind and consequently modulate the polar wind.…”
Section: Introductionmentioning
confidence: 89%
“…André et al (2015) extended the data to cover most parts of the solar cycle 23. These data have been used in several studies (e.g., Haaland et al, 2012Haaland et al, , 2015Li et al, 2012Li et al, , 2013Li et al, , 2017Maes et al, 2017).…”
Section: 1029/2018ja025819mentioning
confidence: 99%